Kajian Komparatif tentang Pengaturan Pelindungan Budaya dalam Konstitusi Negara-Negara Asia Pasifik - Collins, Josua Satria (Jurnal Konstitusi & Demokrasi, 2024)
Culture is a fundamental element in shaping national identity and unity amidst diversity. Therefore, many countries incorporate cultural protection into their constitutions to ensure the sustainability of cultural heritage. The constitution not only serves as a legal foundation but also as a social engineering instrument to facilitate cultural development amid contemporary challenges. This study focuses on the Asia-Pacific region due to its high cultural diversity and the complex interaction between local traditions and globalization. Using a normative juridical method and a comparative approach, the study analyzes 54 constitutions from countries in the region. The findings indicate that the majority of these countries include constitutional provisions related to culture, following three main trends: (1) representation of cultural practitioners in parliament, (2) preservation of cultural and historical sites, and (3) guaranteed access to cultural education and research. Compared to Indonesia, some countries have more detailed regulations regarding the protection of historical sites and support for cultural research and education. This study recommends strengthening cultural protection in Indonesia’s constitution by adopting best practices from other countries, ensuring more effective preservation of national identity and cultural advancement in the face of globalization.